Those Who Have No Chains to Lose: Precarious Paid Teachers and Master Instructors - Ersin Yagan (Anı Publishing, 2022)
The term "precariat" refers to a group of employees who work in non-permanent jobs and do not have a steady source of income. According to the literature, the situation of paid teachers and master trainers working in public formal and non-formal education institutions was investigated in this study. The research was conducted with ten paid instructors and ten master instructors who worked for hourly salaries in Istanbul's schools and public education centers. The content analysis method, which is one of the qualitative research methods, was used to conduct the research. The information was gathered using a semi-structured interview form and a face-to-face interview technique. As a result of the data analysis, it was found that paid teachers and master instructors acted as denizen citizens. Personnel and trade union rights were the most prominent themes among the participants. When the research findings are considered, it is possible to conclude that eliminating low-wage occupations and security concerns will increase the quality of paid teachers and master instructors, as well as the educational system as a whole.